Implementation of PID Controllers on the Motorola DSP56000/ DSP56001, Part 1 - Stokes, Jay; Sohie, Guy R. L. (Microprocessors & Microsystems, 1991)
The use of the Motorola DSP56000/DSP56001 for solving real-time digital control problems is discussed, particularly regarding the implementation of general control algorithms such as PID controllers and notch filters